A world of lies - Aavik, Toivo (2006)
This article reports two worldwide studies of stereotypes about liars. These studies are carried out in 75 different countries and 43 different languages. In Study 1, participants respond to the open-ended question "How can you tell when people are lying?" In Study 2, participants complete a questionnaire about lying. These two studies reveal a dominant pan-cultural stereotype: that liars avert gaze. The authors identify other common beliefs and offer a social control interpretation.